The role of dipole interactions in hyperthermia heating colloidal clusters of densely-packed superparamagnetic nanoparticles - Fu, Rong; Yan, Yuying; Roberts, Clive; Liu, Zeyu; Chen, Yiyi (Nature Publishing Group, 2018)
This work aims to investigate the influence of inter-particle dipole interactions on hyperthermia heating colloidal clusters of densely-packed Fe3O4 nanoparticles at low field intensity. Emulsion droplet solvent evaporation method was used to assemble oleic acid modified Fe3O4 particles into compact clusters which were stabilized by surfactant in water. Both experimental and simulation works were conducted to study their heating performance at different cluster’s sizes. The dipole interactions improve the heating only when the clusters are small enough to bring an enhancement in clusters’ shape anisotropy. The shape anisotropy is reduced at greater clusters’ sizes, since the shapes of the clusters become more and more spherical. Consequently, the dipole interactions change to impair the heating efficiency at larger sizes. When the clusters are totally isotropic in shape, the heating efficiency is lower than that of non-interacting particles despite the cluster’s size, although the efficiency increases by a little bit at a particular size most likely due to the dipole couplings. In these situations, one has to use particles with higher magnetic anisotropy and/or saturation magnetization to improve the heating.